Karakteristik Batuan Ultrabasa Di Desa Winatu Dan Kamarora, Kabupaten Sigi, Provinsi Sulawesi Tengah - Eksel Setiawan Mareoli; Riska Puspita; Ninasafitri Ninasafitri (Jurnal Teknologi Sumberdaya Mineral, 2022)
Ultramafic rocks are found in Sigi district in the Kamarora and Winatu areas but are not mentioned in the regional geology of the Poso sheet and the Pasangkayu sheet so that it is interesting to investigate further. Therefore, it is important to conduct this research to determine the characteristics and processes of ultramafic rock formation in the Kamarora and Winatu areas of Sigi district using the Petrographic and X-Ray Fluorescence (XRF) methods. The results of this study are based on petrographic analysis of two rock samples in Kamarora Village containing olivine (60-55%), omphasite (15-10%), enstatite (5%), serpentine (10%), garnet (15-10%) ) and chlorite (5%) with the rock name lherzolite, while one rock sample in Winatu Village contained serpentine minerals (75%), olivine (15%), omphasite (5%), enstasite (5%) with serpentine rock names. The chemical composition and percentage of each element of the samples analyzed by XRF stations ST01K, ST02K, ST01W are as follows: major element SiO2 (40 – 41.1 wt %), Al2O3 (2.90 – 19.6 wt %), Fe2O3 (7 – 9.98 wt %), MgO (17 – 33.7 wt %), CaO (11.30 – 12.4 wt %), Na2O (0.147–2.11 wt %), K2O (0.0558 – 0.234 wt %) and minor elements with a content range of TiO2 (0.104 – 0.965 wt %), MnO (0.102 – 0.145 wt%), SO3 (0.0719 – 0.259 wt %), Cl ( 0.0954 – 0.360 wt %), NiO (0.0272 – 0.307 wt %), Cr2O3 (0.111 – 0.403 wt %), Co2O3 (0.0246 wt %), WO3 (0.0563 – 0.0661 wt %). Rocks formed in the type of tholeiite magma, this type of magma has a low potassium content, usually formed in subduction and non-subduction areas. Based on the results of the plot on the Pearce et al (1976) diagram, it is known that the tectonic order of rock formation is on the ocean ridge and floor or the expansion of the ocean floor.